Fabrication and Characterization of Psf-TiO2/GO Membranes for Photocatalytic Decomposition of Dyes in Batik Liquid Waste - Arofah, Rosyida Nofiana; Rahmawat, Yeni; Taufany, Fadlilatul; Nurkhamidah, Siti (Eksergi, 2025)
One of the important processes in making batik cloth is dyeing which requires large amounts of water. Liquid waste from washing and rinsing batik cloth produces color from residual dye and can be the main source of water pollution. One method of removing dyes is the ultrafiltration process using Membrane Technology for photocatalytic decomposition. In this research, polysulfone (PSf) membrane uses addition of different TiO2 compositions (1, 1.5, 2, 3, and 5 wt.%) and graphene oxide (GO) of 0.5 wt.% composition as photocatalyst. The photocatalyst can store energy therefore the photocatalytic process can be performed in a visible light environment. To identify the best composition of photocatalysts, photocatalytic performances were tested by the removal of methyl violet as dye along with characterization of the membranes for the morphological and physicochemical properties using FTIR, SEM, XRD, and DMA. The highest performance under visible light was shown by a membrane containing 5 wt.% TiO2, which provided a permeate flux of 22.97 L m-2 h-1 and dye removal of up to 89.84%. The findings indicated that the PSf membrane matrix's stability and photocatalytic enhanced potential are driven by the cooperative interaction between TiO2 and GO nanoparticles, which function as photocatalysts.